Preparation method of sodium ferrous fluorophosphate, preparation method of sodium ferrous fluorophosphate positive electrode material
Sodium fluoride is prepared by reacting the fluorosilicate solution produced by phosphorus chemical chemical by-product with sodium carbonate, and mixed with hydrofluoric acid and phosphoric acid in water, and the existing preparation methods for ferrous phosphate positive electrode materials are successfully solved, and the preparation of high purity and uniform particle size is achieved, which is suitable for high-performance materials for sodium ion batteries.
Patent Information
- Application Number
- CN202310481932.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-04-28
- Publication Date
- 2025-04-29
- Estimated Expiration
- 2043-04-28
AI Technical Summary
The existing preparation methods of sodium ferrous fluorophosphate positive electrode materials have problems such as complex process, high cost, and insufficient product purity and particle size uniformity.
Sodium fluoride is prepared by reacting a solution of fluorosilicate produced by phosphorus chemical industry with sodium carbonate, and then reacting with hydrofluoric acid to form sodium hydrogen fluoride. Finally, under the protection of an inert gas, it is mixed with phosphoric acid and ferrous oxide in water to prepare sodium ferrous phosphate.
The preparation of sodium ferrous phosphate is achieved with simple process, low cost, high product purity and good particle size uniformity. It is suitable for large-scale production and improves the reversible specific capacity and capacity retention rate of sodium ion batteries.
Smart Images

Figure CN116495717B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a method for preparing sodium ferrous fluorophosphate and a method for preparing a sodium ferrous fluorophosphate positive electrode material, and belongs to the technical field of battery material preparation. Background Art
[0002] In recent years, sodium-ion batteries, which have the same working principle and similar battery components as lithium-ion batteries, have attracted extensive attention from researchers due to their advantages such as abundant sodium resources, low cost and good comprehensive performance. In addition, sodium-ion batteries can well meet the requirements of low cost, long life and high safety performance in the field of new energy, and can alleviate the problem of limited development of energy storage batteries caused by the shortage of lithium resources to a certain extent. Among the sodium-ion battery cathode materials developed and studied, it was found that sodium-based fluorinated phosphate system compounds have good electrochemical properties. At the same time, under the induction of fluoride ions, the theoretical energy density can reach 450Wh / kg. With its stable three-dimensional structure, sodium ferrous fluorophosphate cathode material shows excellent long-cycle stability and rate characteristics in the half-cell system, and has good application prospects. Sodium ferrous fluorophosphate cathode materials are usually made of carbon-coated sodium ferrous fluorophosphate, which can improve the electronic conductivity of sodium ferrous fluorophosphate.
[0003] The preparation methods of sodium ferrous fluorophosphate positive electrode materials generally include solid phase method, coprecipitation method, sol-gel method and ion thermal synthesis method. The solid phase method has become the first choice among many methods due to its simple operation, short process flow and low cost. However, this method has long calcination time, high energy consumption, low efficiency and poor uniformity of product morphology and particle size. The coprecipitation method, sol-gel method and ion thermal synthesis method all require the raw materials to be soluble raw materials, and there are many conditions to be controlled in the process, and the energy consumption is high.
[0004] Therefore, there is an urgent need to develop a preparation method for sodium ferrous fluorophosphate with simple process, low cost, high product purity and good particle size uniformity. Summary of the invention
[0005] The object of the present invention is to provide a method for preparing sodium ferrous fluorophosphate with simple process, low cost, high product purity and good particle size uniformity.
[0006] Another object of the present invention is to provide a method for preparing sodium ferrous fluorophosphate positive electrode material.
[0007] In order to achieve the above purpose, the technical solution adopted by the preparation method of sodium ferrous fluorophosphate of the present invention is:
[0008] A method for preparing sodium ferrous fluorophosphate comprises the following steps:
[0009] (1) preparing sodium fluoride by reacting a fluorosilicic acid solution with a sodium salt; the fluorosilicic acid solution is a fluorosilicic acid solution produced as a byproduct of a phosphorus chemical industry and / or a fluorosilicic acid solution produced as a byproduct of a fluorine chemical industry; the sodium salt is sodium carbonate and / or sodium bicarbonate; the fluorosilicic acid solution contains iron ions, sodium ions, calcium ions, magnesium ions and manganese ions;
[0010] (2) reacting the sodium fluoride obtained in step (1) with hydrofluoric acid to prepare sodium bifluoride;
[0011] (3) Under the protection of an inert gas, the sodium bifluoride, phosphoric acid and ferrous oxide prepared in step (2) are mixed in water for reaction to obtain sodium ferrous fluorophosphate.
[0012] The preparation method of sodium ferrous fluorophosphate of the present invention, using fluorosilicic acid produced by phosphorus chemical industry and / or fluorosilicic acid produced by fluorine chemical industry to prepare high value-added sodium ferrous fluorophosphate, can solve the problem of fluorosilicic acid treatment, because the by-product fluorosilicic acid contains sulfate, phosphate and a small amount of calcium, sodium, magnesium, manganese, iron and other impurities, must be removed before use during use, and when used to prepare sodium ferrous fluorophosphate for sodium ion battery, these impurities are the effective components of battery materials, all do not need to be pre-treated, and trace impurities play the effect of doping for battery materials, which opens up new space for the effective application of fluorosilicic acid. Among them, calcium, magnesium, and manganese divalent metal ions do not change price during charging and discharging, mainly play a role in stabilizing the structure, and enhance the cyclic stability of the material, while sodium and iron are elements of the positive electrode material itself, which play a role in improving the first effective capacity of the material. The preparation method of sodium ferrous fluorophosphate of the present invention, adopts aqueous solution direct synthesis method to prepare sodium ferrous fluorophosphate, the reaction process is more sufficient, the reaction conditions are mild, the process is simple, the overall time consumption is short, and it is suitable for large-scale production. When the sodium ferrous fluorophosphate prepared by the present invention is used in a sodium ion battery, the sodium ion battery can have a higher reversible specific capacity and capacity retention rate.
[0013] The chemical reaction equation involved in the preparation method of sodium ferrous fluorophosphate of the present invention is as follows:
[0014] (1)H2SiF6+3Na2CO3→6NaF+SiO2+H2O+3CO2↑,
[0015] H2SiF6+6NaHCO3→6NaF+SiO2+4H2O+6CO2↑
[0016] The above chemical reaction is the chemical reaction that occurs when preparing sodium fluoride in step (1);
[0017] (2) NaF+HF→NaHF2, the chemical reaction is the chemical reaction that occurs when sodium bifluoride is prepared in step (2);
[0018] (3) 2NaHF2+H3PO4+FeO→Na2FePO4F+H2O+3HF↑, this chemical reaction is the chemical reaction that occurs when sodium ferrous fluorophosphate is prepared in step (3).
[0019] Preferably, in step (1), after the reaction is completed, the solid and liquid are separated, and the liquid obtained by the solid-liquid separation is dried to obtain sodium fluoride. The solid obtained by the solid-liquid separation is white carbon black. The white carbon black obtained when preparing sodium fluoride in step (1) can be sold as a by-product, or it can react with hydrogen fluoride to generate fluorosilicic acid, and the generated fluorosilicic acid can be used as a raw material in step (1). The chemical reaction equation of the reaction of white carbon black with hydrogen fluoride is as follows: SiO2+6HF→H2SiF6+2H2O.
[0020] Since the reaction between fluorosilicic acid and sodium salt is relatively thorough, in order to avoid material residue and reduce the purity of the prepared sodium fluoride, preferably, in step (1), the ratio of the molar amount of fluorosilicic acid in the fluorosilicic acid solution to the molar amount of sodium in the sodium salt is 1:6.
[0021] Preferably, in step (1), the mass fraction of fluorosilicic acid in the fluorosilicic acid solution is 20% to 30%. If the concentration of the fluorosilicic acid solution is too low, more wastewater will be generated later; if the concentration is too high, the reaction is not complete and lumps are easy to form.
[0022] Generally, the mass fraction of fluorosilicic acid in the fluorosilicic acid solution produced as a by-product of phosphorus chemical industry is lower than 20% (e.g. 15%), and the mass fraction of fluorosilicic acid in the fluorosilicic acid solution produced as a by-product of fluorine chemical industry is higher than 30% (e.g. 42%). In order to obtain a fluorosilicic acid solution with a mass fraction of 20% to 30%, preferably, the fluorosilicic acid solution is prepared by mixing a fluorosilicic acid solution produced as a by-product of phosphorus chemical industry and a fluorosilicic acid solution produced as a by-product of fluorine chemical industry.
[0023] In the present invention, the fluorosilicic acid solution produced as a byproduct of phosphorus chemical industry contains a small amount of impurities, such as sulfate, phosphate, free fluorine, iron ion, arsenic ion, nickel ion, chromium ion and manganese ion. The fluorosilicic acid solution produced as a byproduct of fluorine chemical industry contains a small amount of impurities, such as sulfate, phosphate, free fluorine, iron ion, arsenic ion, sodium ion, calcium ion, magnesium ion, nickel ion and chromium ion.
[0024] Preferably, the content of iron ions in the fluosilicic acid solution is 2 to 20 ppm, the content of sodium ions is 0 to 20 ppm, the content of calcium ions is 0 to 100 ppm, the content of magnesium ions is 0 to 50 ppm, and the content of manganese ions is 0 to 0.3 ppm.
[0025] Preferably, the fluorosilicic acid solution further contains arsenic ions, nickel ions and chromium ions; the content of arsenic ions is 0-1 ppm, the content of nickel ions is 0-0.2 ppm, and the content of chromium ions is 0.2-0.25 ppm.
[0026] Preferably, the fluorosilicic acid solution further contains sulfate ions, and the mass fraction of sulfate ions is 0.1% to 1%.
[0027] Preferably, the fluorosilicic acid solution further contains phosphate ions, and the mass fraction of the phosphate ions is 0.05% to 0.5%.
[0028] Preferably, the fluorosilicic acid solution further contains free fluorine, and the mass fraction of free fluorine is 0.5-3.5% calculated as HF.
[0029] Preferably, in step (1), the reaction temperature is 90-120° C. If the reaction temperature is lower than 90° C., the reaction will be incomplete, and if the reaction temperature is higher than 120° C., the generated SiO2 particles will be agglomerated, the specific surface area will be reduced, and silicon slag will be generated, which will carry sodium fluoride and is difficult to separate.
[0030] Preferably, in step (1), the reaction time is 1 to 5 hours. For example, in step (1), the reaction time is 3 hours.
[0031] In order to avoid the introduction of other impurities, preferably, in step (1), the purity of the sodium salt is not less than 99.8%.
[0032] In order to completely dissolve sodium fluoride to generate sodium bifluoride, preferably, in step (2), the ratio of the molar amount of sodium fluoride to the molar amount of hydrogen fluoride in hydrofluoric acid is 1:(1-1.05). For example, in step (2), the ratio of the molar amount of sodium fluoride to the molar amount of hydrogen fluoride in hydrofluoric acid is 1:1.
[0033] In order to reduce the subsequent generation of wastewater, preferably, in step (2), the mass fraction of the hydrofluoric acid is 40-50%. For example, the mass fraction of the hydrofluoric acid is 40%. In order to avoid the introduction of impurities, the hydrofluoric acid is electronic grade hydrofluoric acid.
[0034] Preferably, in step (2), the reaction is carried out at room temperature.
[0035] In order to fully carry out the reaction and because phosphoric acid has a low cost, preferably, in step (3), the molar ratio of sodium bifluoride, phosphoric acid and ferrous oxide is 2: (1-1.2): 1. For example, in step (3), the molar ratio of sodium bifluoride, phosphoric acid and ferrous oxide is 2: 1: 1.
[0036] Preferably, in step (3), the temperature of the mixed reaction is 90-150° C. If the mixed reaction temperature is lower than 90° C., almost no reaction occurs. If the mixed reaction temperature is higher than 150° C., part of the sodium bifluoride will decompose and hydrogen fluoride will overflow in advance, causing part of the sodium bifluoride to not participate in the reaction.
[0037] Preferably, the phosphoric acid is used in the form of a phosphoric acid solution. Preferably, the mass fraction of the phosphoric acid solution is 85%. Since commercially available phosphoric acid is a colorless, transparent, viscous liquid of 85%, direct use without dilution can reduce the generation of subsequent wastewater. In order to avoid the introduction of impurities, the phosphoric acid is electronic grade phosphoric acid.
[0038] Preferably, the sodium bifluoride is used in the form of a sodium bifluoride solution. Preferably, the mass fraction of the sodium bifluoride solution is 10-15%. Preferably, the sodium bifluoride solution is prepared by mixing sodium fluoride and hydrofluoric acid.
[0039] Preferably, in step (3), the method of mixing reaction comprises the following steps: under the protection of inert gas, firstly mixing the sodium bifluoride, phosphoric acid and ferrous oxide obtained in step (2) in water for reaction for not less than 30 minutes, then adjusting the pH of the system to 6.5-7.5, and continuing the mixing reaction for 3-5 hours. Since the target product is generated only under slightly acidic or neutral conditions, and the target product is not generated or the reaction effect is poor under acidic or alkaline conditions, it is necessary to conduct a preliminary mixing reaction on the reactants, and after 30 minutes, adjust the pH of the system to 6.5-7.5, and continue the mixing reaction, so as to improve the conversion rate.
[0040] Preferably, in step (3), the mixed reaction method comprises the following steps: first adding ferrous oxide to a phosphoric acid solution, then adding a sodium bifluoride solution, and then heating to a temperature required for the mixed reaction. After the mixed reaction is carried out for no less than 30 minutes, the pH of the system is adjusted to 6.5 to 7.5, and the mixed reaction is continued for 3 to 5 hours.
[0041] Preferably, in step (3), the pH adjusting agent used to adjust the pH of the system to 6.5-7.5 is sodium hydroxide, sodium carbonate or sodium bicarbonate.
[0042] Preferably, the preparation method of sodium ferrous fluorophosphate further comprises the following steps: in step (3), after the mixing reaction is completed, the mixture is allowed to stand for 3 to 5 hours, solid-liquid separation is performed, and then the solid obtained by the solid-liquid separation is washed and dried to obtain sodium ferrous fluorophosphate. Standing for 3 to 5 hours can make the crystals of the target product grow, which is beneficial to the subsequent solid-liquid separation.
[0043] Preferably, the solid-liquid separation is centrifugation or filtration. Preferably, the washing is washing the solid obtained by the solid-liquid separation until the concentration of HF in the washing liquid is 0 ppm.
[0044] Preferably, the particle size of the sodium ferrous fluorophosphate is 0.3-6 μm.
[0045] Preferably, the sodium ferrous fluorophosphate contains iron ions, sodium ions, arsenic ions, potassium ions, calcium ions, magnesium ions, nickel ions, chromium ions, copper ions, lead ions, zinc ions, aluminum ions, cadmium ions, manganese ions, and cobalt ions; the mass fractions of the arsenic ions, potassium ions, nickel ions, chromium ions, copper ions, lead ions, zinc ions, cadmium ions, manganese ions, and cobalt ions are all not more than 1 ppm, the mass fractions of the calcium ions and magnesium ions are all not more than 10 ppm, and the mass fraction of the aluminum ions is not more than 2 ppm.
[0046] The technical solution adopted in the preparation method of the sodium ferrous fluorophosphate positive electrode material of the present invention is:
[0047] A method for preparing a sodium ferrous fluorophosphate positive electrode material comprises the following steps:
[0048] The surface of the sodium ferrous fluorophosphate prepared by the above-mentioned preparation method of sodium ferrous fluorophosphate is coated with a carbon layer to obtain a sodium ferrous fluorophosphate positive electrode material.
[0049] The preparation method of the sodium ferrous fluorophosphate positive electrode material of the present invention directly coats a carbon layer on the surface of the sodium ferrous fluorophosphate, wherein the carbon layer can improve the electronic conductivity of the material and can buffer the stress change of the material during the charge and discharge process, and the sodium ferrous fluorophosphate can provide a high theoretical specific capacity. When the prepared sodium ferrous fluorophosphate positive electrode material is used in a sodium ion battery, the sodium ion battery can have a higher reversible specific capacity and capacity retention rate. In a voltage window of 2.0V to 3.8V, when cycled at a rate of 0.2C, the first cycle discharge specific capacity is above 115mAh / g, and the capacity retention rate after 200 cycles is above 92%.
[0050] Preferably, the mass fraction of the carbon layer in the sodium ferrous fluorophosphate positive electrode material is 2.0% to 4.0%.
[0051] Preferably, the method for coating the carbon layer comprises the following steps: mixing the sodium ferrous fluorophosphate prepared by the preparation method of the sodium ferrous fluorophosphate and a carbon precursor material, and then sintering them under an inert atmosphere. The preparation method of the sodium ferrous fluorophosphate positive electrode material of the present invention uses fluorosilicic acid, a byproduct of phosphate fertilizer, as a fluorine source, stirs the sodium ferrous fluorophosphate by a room temperature liquid phase method, and calcines to obtain the target product. The reaction process is more sufficient and mild, the process is simple, the time consumption is short, and it is suitable for large-scale batch production.
[0052] Preferably, the carbon precursor material is selected from one or any combination of sucrose, glucose, fructose and ascorbic acid.
[0053] Preferably, the mixing is performed by ball milling. Preferably, the rotation speed of the ball milling is 300 rpm / min. Preferably, the time of the ball milling is 2.5 h.
[0054] Preferably, the sintering time is 3 hours.
[0055] Preferably, the heating rate from room temperature to the sintering temperature is 2° C. / min. BRIEF DESCRIPTION OF THE DRAWINGS
[0056] Figure 1 This is a schematic diagram of the appearance of the sodium ferrous fluorophosphate powder prepared in Example 1 of the present invention;
[0057] Figure 2 Schematic diagram of the particle size analysis results of the sodium ferrous fluorophosphate powder prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0058] The technical solution of the present invention is further described below in conjunction with specific embodiments.
[0059] The electronic-grade hydrofluoric acid solution used in Examples 1-3 of the present invention and Comparative Example 1 complies with the provisions of standard HGT4509-2013 "Industrial High-Purity Hydrofluoric Acid", and the electronic-grade phosphoric acid solution complies with the provisions of standard GB / T28159-2011 "Electronic-Grade Phosphoric Acid".
[0060] The fluorosilicic acid solution used in Examples 1-3 is prepared by mixing a fluorosilicic acid solution produced as a by-product of phosphorus chemical industry and a fluorosilicic acid solution produced as a by-product of fluorine chemical industry, wherein the mass fraction of fluorosilicic acid and the type and content of impurity ions in the fluorosilicic acid solution produced as a by-product of phosphorus chemical industry and the fluorosilicic acid solution produced as a by-product of fluorine chemical industry are shown in Table 1.
[0061] Table 1 Mass fraction of fluorosilicic acid and type and content of impurity ions in fluorosilicic acid solution produced as a byproduct of phosphorus chemical industry and fluorosilicic acid solution produced as a byproduct of fluorine chemical industry
[0062]
[0063] 1. The specific embodiment of the preparation method of sodium ferrous fluorophosphate of the present invention is as follows:
[0064] Example 1
[0065] The preparation method of sodium ferrous fluorophosphate of the present embodiment specifically comprises the following steps:
[0066] (1) Add 100 kg of 20% by mass fluorosilicic acid solution and 44.25 kg of 99.8% high-purity sodium carbonate into reactor No. 1, heat to 90° C., stir and react for 3 h, centrifuge and separate the layers, and take out the lower layer of sodium fluoride aqueous solution, the mass of sodium fluoride in the sodium fluoride aqueous solution is 38 kg;
[0067] (2) filtering the sodium fluoride aqueous solution obtained in step (1), then washing the filtered solid twice with pure water, and then drying the washed solid at 120° C. for 2 h to obtain 34.5 kg of sodium fluoride solid powder; the upper layer of white carbon black aqueous solution is filtered, washed, and dried, and then sold or directly added with anhydrous hydrogen fluoride to synthesize fluorosilicic acid solution and returned to step (1);
[0068] (3) dissolving the sodium fluoride powder obtained in step (2) into 41.07 kg of 40% electronic grade hydrofluoric acid solution, adding 433.73 kg of ultrapure water and stirring to obtain a 10% sodium bifluoride aqueous solution;
[0069] (4) Add 47.35 kg of 85% electronic grade phosphoric acid solution into the No. 2 reactor, then add 29.57 kg of FeO powder, and introduce nitrogen (nitrogen flow rate is 3 L / min) into the No. 2 reactor to protect the ferrous ions, then slowly add (addition rate is 10 mL / min) the sodium bifluoride aqueous solution prepared in step (3) under low speed stirring, after all the additions are completed, heat to 90° C., increase the stirring speed to 300 rpm, stir for 30 min, add 10 mL of 4 mol / L NaOH The solution was prepared by adjusting the pH value of the mixed solution in the No. 2 reactor to 6.5, and stirring was continued for 3 hours to obtain a gel-like dilute solution. After standing for 5 hours, the upper aqueous solution was removed by centrifugation. The solid obtained by centrifugation was in the form of an ointment with a mass of 97 g. The ointment-like solid was washed three times with pure water. The mass of pure water used for each washing was 1.5 times the mass of the ointment-like solid. The HF concentration in the washing liquid obtained from the last washing was 0 ppm. The washed solid was then dried at 120°C for 2 hours to obtain 86.7 kg of sodium ferrous fluorophosphate powder. The appearance of the sodium ferrous fluorophosphate powder is shown in the figure. Figure 1 As shown in Figure 2, the particle size analysis results of sodium ferrous fluorophosphate powder (particle size analyzer test results) are as follows: Figure 2 As shown, the median particle size D50 is 1.53 μm, and the particle size distribution range is 0.3 to 6 μm (some agglomeration may occur).
[0070] Example 2
[0071] The preparation method of sodium ferrous fluorophosphate of the present embodiment specifically comprises the following steps:
[0072] (1) Add 100 kg of 25% by mass fluorosilicic acid solution and 55.32 kg of high-purity sodium carbonate with a purity of 99.8% to reactor No. 1, heat to 100° C., stir and react for 3 h, centrifuge and separate the layers, and take out the lower layer of sodium fluoride aqueous solution. The mass of sodium fluoride in the sodium fluoride aqueous solution is 47.75 kg;
[0073] (2) filtering the sodium fluoride aqueous solution obtained in step (1), then washing the filtered solid twice with pure water, and then drying the washed solid at 120° C. for 2 h to obtain 43.15 kg of sodium fluoride solid powder; the upper layer of white carbon black aqueous solution is filtered, washed, and dried, and then sold or directly added with anhydrous hydrogen fluoride to synthesize fluorosilicic acid solution and returned to step (1);
[0074] (3) dissolving the sodium fluoride powder obtained in step (2) into 51.37 kg of electronic grade hydrofluoric acid solution having a mass fraction of 40%, adding 436.31 kg of ultrapure water and stirring to obtain a sodium bifluoride aqueous solution having a mass fraction of 12%;
[0075] (4) Add 59.23 kg of 85% electronic grade phosphoric acid solution into the No. 2 reactor, then add 36.99 kg of FeO powder, and introduce nitrogen (nitrogen flow rate is 3 L / min) into the No. 2 reactor to protect the ferrous ions, then slowly add (addition rate is 10 mL / min) the sodium bifluoride aqueous solution prepared in step (3) under low speed stirring, after all the additions are completed, heat to 120° C., increase the stirring speed to 400 rpm, stir for 30 min, add 15 mL of 4 molar concentration of sodium bifluoride. l / L NaOH solution, adjust the pH value of the mixed solution in reactor No. 2 to 7.0, continue stirring for 4 hours, and obtain a gel-like dilute solution. After standing for 3 hours, remove the upper aqueous solution by centrifugation. The solid obtained by centrifugation is in the form of an ointment with a mass of 122g. The ointment-like solid is washed three times with pure water. The mass of pure water used for each washing is 1.5 times the mass of the ointment-like solid. The HF concentration in the washing liquid obtained from the last washing is 0ppm. The washed solid is then dried at 120°C for 2 hours to obtain 109.96kg of sodium ferrous fluorophosphate powder.
[0076] Example 3
[0077] The preparation method of sodium ferrous fluorophosphate of the present embodiment specifically comprises the following steps:
[0078] (1) Add 100 kg of 30% by mass fluorosilicic acid solution and 66.38 kg of high-purity sodium carbonate with a purity of 99.8% to reactor No. 1, heat to 120° C., stir and react for 3 h, centrifuge and separate the layers, and take out the lower layer of sodium fluoride aqueous solution. The mass of sodium fluoride in the sodium fluoride aqueous solution is 56.5 kg;
[0079] (2) filtering the sodium fluoride aqueous solution obtained in step (1), then washing the filtered solid twice with pure water, and then drying the washed solid at 120° C. for 2 h to obtain 52 kg of sodium fluoride solid powder; the upper layer of white carbon black aqueous solution is filtered, washed, and dried, and then sold or directly added with anhydrous hydrogen fluoride to synthesize fluorosilicic acid solution and returned to step (1);
[0080] (3) dissolving the sodium fluoride powder obtained in step (2) into 61.90 kg of an electronic grade hydrofluoric acid solution having a mass fraction of 40%, adding 397.85 kg of ultrapure water and stirring to obtain a sodium bifluoride aqueous solution having a mass fraction of 15%;
[0081] (4) Add 71.37 kg of 85% electronic grade phosphoric acid solution to reactor No. 2, and then add 44.57 kg FeO powder, and nitrogen (nitrogen flow rate is 3L / min) is introduced into the No. 2 reactor to protect the ferrous ions, and then the sodium bifluoride aqueous solution obtained in step (3) is slowly added (addition rate is 10mL / min) under low speed stirring, and the temperature is raised to 150°C after all the addition is completed, the stirring speed is increased to 500rmp / min, and after stirring for 30min, 20mL of NaOH solution with a concentration of 4mol / L is added, and the pH value of the mixed solution in the No. 2 reactor is adjusted to 7.5, and stirring is continued for 5h to obtain a gel-like dilute solution. After standing for 4h, the upper aqueous solution is removed by centrifugation, and the solid obtained by centrifugation is in the form of an ointment with a mass of 148.7g. The ointment-like solid is washed three times with pure water, the mass of pure water used for each washing is 1.5 times the mass of the ointment-like solid, and the HF concentration in the washing liquid obtained by the last washing is 0ppm, and then the washed solid is dried at 120°C for 2h to obtain 130.7kg of sodium ferrous fluorophosphate powder.
[0082] The content of metal ions in the sodium ferrous fluorophosphate powder prepared in this example was detected by ICP, and the results are shown in Table 2;
[0083] Table 2 Content of metal ions in sodium ferrous fluorophosphate powder prepared in Example 3
[0084]
[0085] 2. The specific embodiment of the preparation method of the sodium ferrous fluorophosphate positive electrode material of the present invention is as follows:
[0086] Example 4
[0087] The preparation method of the sodium ferrous fluorophosphate positive electrode material of this embodiment specifically comprises the following steps:
[0088] (1) 86.7 kg of sodium ferrous fluorophosphate prepared in Example 1 and glucose were ball-milled at a mass ratio of 5:1, the rotation speed was controlled at 300 rpm, and the time was 2.5 h. Then, the ball-milled mixed materials were placed in a tubular furnace, argon was introduced, and the temperature was raised to 600° C. at a rate of 2° C. / min. The temperature was kept for 3 h, and 88.43 kg of sodium ferrous fluorophosphate positive electrode material was obtained after natural cooling.
[0089] Example 5
[0090] The preparation method of the sodium ferrous fluorophosphate positive electrode material of this embodiment specifically comprises the following steps:
[0091] (1) 109.96 kg of sodium ferrous fluorophosphate prepared in Example 2 and ascorbic acid were ball-milled at a mass ratio of 5:1, the rotation speed was controlled at 300 rpm, and the time was 2.5 h. Then, the ball-milled mixed materials were placed in a tubular furnace, argon was introduced, and the temperature was raised to 600° C. at a rate of 2° C. / min. The temperature was kept for 3 h, and 113.25 kg of sodium ferrous fluorophosphate positive electrode material was obtained after natural cooling.
[0092] Example 6
[0093] The preparation method of the sodium ferrous fluorophosphate positive electrode material of this embodiment specifically comprises the following steps:
[0094] (1) 130.7 kg of sodium ferrous fluorophosphate prepared in Example 3 and sucrose were ball-milled at a mass ratio of 5:1, the rotation speed was controlled at 300 rpm, and the time was 2.5 h. Then, the ball-milled mixed materials were placed in a tubular furnace, argon was introduced, and the temperature was raised to 600° C. at a rate of 2° C. / min. The temperature was kept for 3 h, and 135.93 kg of sodium ferrous fluorophosphate positive electrode material was obtained after natural cooling.
[0095] Comparative Example 1
[0096] The preparation method of the sodium ferrous fluorophosphate positive electrode material of this comparative example specifically comprises the following steps:
[0097] (1) taking high-purity sodium bifluoride solid, preparing 509.3 kg of sodium bifluoride aqueous solution with a mass fraction of 10%;
[0098] (2) This step is the same as step (4) of Example 1;
[0099] (3) 86.2 kg of sodium ferrous fluorophosphate prepared in step (2) and glucose were ball-milled at a mass ratio of 5:1, the rotation speed was controlled at 300 rpm, the time was 2.5 h, and then the ball-milled mixed materials were placed in a tubular furnace, argon was introduced, the temperature was raised to 600 ° C at a rate of 2 ° C / min, and the temperature was kept for 3 h. After natural cooling, 88.2 kg of sodium ferrous fluorophosphate positive electrode material was obtained.
[0100] Comparative Example 2
[0101] The preparation method of the sodium ferrous fluorophosphate positive electrode material of this comparative example specifically comprises the following steps:
[0102] (1) taking high-purity sodium bifluoride solid, high-purity ferric sulfate, high-purity sodium sulfate, high-purity calcium sulfate, high-purity magnesium sulfate, nickel sulfate hexahydrate, chromium sulfate hexahydrate and manganese sulfate monohydrate, dissolving them in water, and then adding an appropriate amount of high-purity hydrofluoric acid to obtain a sodium bifluoride aqueous solution with a mass fraction of sodium bifluoride of 10%, the mass of the sodium bifluoride aqueous solution is 509.3 kg, and the mass fraction of hydrogen fluoride in the sodium bifluoride aqueous solution is the same as the mass fraction of hydrogen fluoride in the sodium bifluoride aqueous solution in step (3) of Example 3;
[0103] (2) This step is the same as step (4) of Example 3. After ICP detection, the mass fraction of metal ions (iron ions, arsenic ions, sodium ions, potassium ions, calcium ions, magnesium ions, nickel ions, chromium ions, copper ions, lead ions, zinc ions, aluminum ions, cadmium ions, manganese ions, and cobalt ions) in the sodium ferrous fluorophosphate prepared in this step is not more than 0.05 ppm compared with the mass fraction of the same metal ions in the sodium ferrous fluorophosphate micropowder prepared in Example 3, and the mass fraction of sulfate ions in the sodium ferrous fluorophosphate prepared in this step is not more than 0.05 ppm compared with the mass fraction of sulfate ions in the sodium ferrous fluorophosphate micropowder prepared in Example 3.
[0104] (3) The sodium ferrous fluorophosphate prepared in step (2) with a mass of 130.7 kg and sucrose were ball-milled at a mass ratio of 5:1, the rotation speed was controlled at 300 rpm, and the time was 2.5 hours. Then, the ball-milled mixed materials were placed in a tubular furnace, argon was introduced, and the temperature was raised to 600° C. at a rate of 2° C. / min. The temperature was kept for 3 hours, and the sodium ferrous fluorophosphate positive electrode material was obtained after natural cooling.
[0105] Comparative Example 3
[0106] The preparation method of the sodium ferrous fluorophosphate positive electrode material of this comparative example specifically comprises the following steps:
[0107] 500 g of sodium fluoride solid was added to the ball mill, followed by FeC2O4·2H2O and ammonium dihydrogen phosphate, the molar ratio of sodium fluoride, FeC2O4·2H2O and ammonium dihydrogen phosphate being 2:1:1, and then 1285 g of 10% sucrose aqueous solution was added as a carbon source, and then iron balls 8 times the mass of the raw materials were weighed, alcohol was used as a dispersant, and the ball milling was carried out at a speed of 580 rpm for 6 h, and then the ball-milled material was placed in a tubular furnace, argon was introduced, and the mixture was heated at 2°C. The temperature was raised to 600°C at a rate of 2°C / min, kept warm for 3 hours, and naturally cooled to obtain a ferrous fluorophosphate composite material. The ferrous fluorophosphate composite material was then placed in a ball mill, and iron balls 8 times the mass of the raw materials were added. Alcohol was used as a dispersant, and the material was ball milled at a speed of 580 rpm for 4 hours. The ball-milled material was then placed in a tubular furnace, argon was introduced, and the temperature was raised to 600°C at a rate of 2°C / min, kept warm for 10 hours, and then taken out and ground into powder to obtain a sodium ferrous fluorophosphate positive electrode material.
[0108] Experimental example
[0109] In order to evaluate the electrochemical performance of the sodium ferrous fluorophosphate positive electrode materials prepared in Examples 4-6 and Comparative Examples 1-3, the sodium ferrous fluorophosphate positive electrode materials were prepared into CR2025 type sodium ion button batteries, and then the battery's first cycle discharge specific capacity and capacity retention rate after 200 cycles were tested at a voltage window of 2.0V to 3.8V and a 0.2C rate cycle. The active material on the positive electrode sheet of the CR2025 type button battery is made of a mixture of sodium ferrous fluorophosphate positive electrode material, polyvinylidene fluoride PVDF and carbon nanotubes CNT in a mass ratio of 10:1:1, the negative electrode sheet is metallic sodium, and the electrolyte is made of sodium hexafluorophosphate, ethylene carbonate and diethyl carbonate, the concentration of sodium hexafluorophosphate is 1 mol / L, and the mass ratio of ethylene carbonate and diethyl carbonate is 1:1.
[0110] The test results of the first cycle discharge specific capacity and the capacity retention rate after 200 cycles of the sodium ion batteries made of the sodium ferrous fluorophosphate positive electrode materials prepared in Examples 4-6 and Comparative Examples 1-3 are shown in Table 3.
[0111] Table 3 First cycle discharge specific capacity of sodium ion batteries made of sodium ferrous fluorophosphate positive electrode materials prepared in Examples 4-6 and Comparative Examples 1-3 and capacity retention rate after 200 cycles
[0112]
[0113]
[0114] It can be seen from Table 3 that the first cycle discharge specific capacity of the sodium ion battery made of the sodium ferrous fluorophosphate positive electrode material prepared in Examples 4-6 is 10%-15% higher than the first cycle discharge specific capacity of the sodium ion battery made of the sodium ferrous fluorophosphate positive electrode material prepared in Comparative Examples 1-3, and the capacity retention rate after 200 cycles reaches more than 92%.
Claims
1. A method for preparing sodium ferrous fluorophosphate, characterized in that: The following steps are involved: (1) reacting a fluorosilicic acid solution with a sodium salt at 90-120° C. to prepare sodium fluoride; the fluorosilicic acid solution is a fluorosilicic acid solution produced as a byproduct of phosphorus chemical industry and / or a fluorosilicic acid solution produced as a byproduct of fluorine chemical industry; the sodium salt is sodium carbonate and / or sodium bicarbonate; the fluorosilicic acid solution contains iron ions, sodium ions, calcium ions, magnesium ions and manganese ions; (2) reacting the sodium fluoride prepared in step (1) with hydrofluoric acid to prepare sodium bifluoride; the ratio of the molar amount of the sodium fluoride to the molar amount of the hydrogen fluoride in the hydrofluoric acid is 1:(1-1.05); (3) Under the protection of inert gas, the sodium bifluoride, phosphoric acid and ferrous oxide prepared in step (2) are mixed and reacted in water at 90-150° C. for not less than 30 min, and then the pH of the system is adjusted to 6.5-7.5, and the mixing reaction is continued for 3-5 h to obtain sodium ferrous fluorophosphate; the molar ratio of the sodium bifluoride, phosphoric acid and ferrous oxide is 2:(1-1.2):
1.
2. The method for preparing sodium ferrous fluorophosphate according to claim 1, wherein The phosphoric acid is used in the form of a phosphoric acid solution; and the sodium bifluoride is used in the form of a sodium bifluoride solution.
3. The method for preparing sodium ferrous fluorophosphate as claimed in claim 2, characterized in that: The mass fraction of the sodium bifluoride solution is 10-15%.
4. The method for preparing sodium ferrous fluorophosphate as claimed in claim 2, characterized in that: In step (3), the mixed reaction method comprises the following steps: under the protection of inert gas, first adding ferrous oxide to a phosphoric acid solution, then adding a sodium bifluoride solution, and then heating to a temperature required for the mixed reaction. After the mixed reaction is carried out for no less than 30 minutes, the pH of the system after the reaction is adjusted to 6.5-7.5, and the mixed reaction is continued for 3-5 hours.
5. The method for preparing sodium ferrous fluorophosphate according to any one of claims 1 to 4, characterized in that: The preparation method of sodium ferrous fluorophosphate further comprises the following steps: in step (3), after the mixing reaction is completed, the mixture is allowed to stand for 3 to 5 hours, solid-liquid separation is performed, and then the solid obtained by the solid-liquid separation is washed and dried to obtain sodium ferrous fluorophosphate.
6. The method for preparing sodium ferrous fluorophosphate as claimed in claim 5, characterized in that: The washing is to wash the solid obtained by solid-liquid separation until the concentration of HF in the washing liquid is 0 ppm.
7. A method for preparing a sodium ferrous fluorophosphate positive electrode material, characterized in that: The following steps are involved: The surface of the sodium ferrous fluorophosphate prepared by the method for preparing sodium ferrous fluorophosphate according to any one of claims 1 to 6 is coated with a carbon layer to obtain a sodium ferrous fluorophosphate positive electrode material.
8. The method for preparing the sodium ferrous fluorophosphate positive electrode material according to claim 7, characterized in that: The mass fraction of the carbon layer in the sodium ferrous fluorophosphate positive electrode material is 2.0% to 4.0%.
Citation Information
Patent Citations
Method for preparing carbon coated nano rodlike sodium ferrous phosphate material by solvent thermal
CN106058249A
Preparation method of cobalt-doped sodium ferrous fluorophosphate positive material
CN108832112A